Electronic Stuctures: Mechanically Guided Post‐Assembly of 3D Electronic Systems (Adv. Funct. Mater. 48/2018). (26th November 2018) - Kim, Bong Hoon; Liu, Fei; Yu, Yongjoon; Jang, Hokyung; Xie, Zhaoqian; Li, Kan; Lee, Jungyup; Jeong, Ji Yoon; Ryu, Arin; Lee, Yechan; Kim, Do Hoon; Wang, Xueju; et al.
Abstract : In article number1803149, Yonggang Huang, Yihui Zhang, John A. Rogers, and co‐workers present deterministic assembly processes for transforming conventional, planar devices based on flexible printed circuit board (FPCB) platforms into those with 3D architectures in a manner that is fully compatible with off‐the‐shelf packaged or unpackaged component parts. The strategy to 3D FPCB technologies creates immediate opportunities for designs in multifunctional systems that leverage state‐of‐the‐art components.